An ITC Study on the Interaction Energy Between Galactomannan Biopolymers and Selected MO2 Nanoparticles in Hydrogels. Issue 8 (14th June 2016) - Hurnaus, Thomas; Plank, Johann
Abstract: The interaction of guar gum, a galactomannan polysaccharide, and its derivative hydroxypropyl guar (HPG) with MO2 nanoparticles whereby M exhibits a decreasing metallic character (Ti → Sn → Si) and MO2 different sizes (6 – 15 nm) was studied by applying isothermal titration calorimetry (ITC) and rotational viscosimetry. It was found that the crosslinking ability of the oxide nanoparticles towards galactomannans is controlled by the electropositive character of M and the size of the nanoparticles which should be as small as possible (< 10 nm) to produce extremely viscous gels. The thermodynamic parameters ΔH, ΔS and ΔG for the association reaction obtained from ITC revealed that the interaction generally is entropy driven, slightly stronger for guar gum than for HPG and is decreasing from TiO2 to SnO2 to SiO2 . The results explain the observations made in the viscosimetric measurements. Abstract : The interaction between galactomannans (guar gum and hydroxypropyl guar) and different MO2 nanoparticles was scrutinized. Isothermal titration calorimetry (ITC) and rotational viscosimetry revealed that the crosslinking ability of MO2 increases with ascending electropositive character of M (Ti > Sn ≫ Si) and decreased size (surface area) of MO2 particles. According to ITC, the crosslinking is entropy driven.